Raton lab, NASA study aviation technology (Raton, NM Raton Range, 1993)
This article is about RIMtech, Inc. (Stolar, Inc.) operating a advanced research and development laboratory in Raton. With information on what type of technology they are working with.
Newspaper article
Master list item #: 63
File location is in the Raton file Cabinet
Keywords: Stolarczyk, Larry -- Director of Research; RIMtech, Inc; Stolar, Inc; Johnson Space Center; NASA (Lyndon B. Johnson Space Center); National Transportation Safety Board (NTSB); Technology Applied to Transportation-related surfaces; Safety Issues; Kelvin -- Smart Technology; Johnson Space Center Technology Utilization Applications Engineering Project; Ice Detection on Airfoil Surfaces; Space Shuttle; Liquid Oxygen Fuel Tanks; General Aviation; Roadway Surfaces; Research Centers; Raton, New Mexico